Preliminary Report from a Randomized Controlled Trial Comparing Two Bovine Pericardial Valves - Sohn, Suk Ho; Kim, Ji Seong; Choi, Jae Woong; Lee, Jae Hang; Kim, Jun Sung; Lim, Cheong; Hwang, Ho Young (The Thoracic and Cardiovascular Surgeon, 2022)
Background A randomized controlled trial was designed to compare 1-year hemodynamic profiles and clinical outcomes after bioprosthetic aortic valve replacement (AVR) using a recently introduced (study group) and world-widely used (control group) bovine pericardial bioprostheses. This study evaluated early postoperative outcomes as a preliminary analysis.Methods The primary end point of the trial was the mean pressure gradient across the aortic valve (AVMPG) at 1 year after surgery. Patients were screened to enroll 70 patients in each group based on a noninferiority design. Early postoperative hemodynamic and clinical outcomes were compared between the two groups.Results There were no differences in baseline characteristics, including sex and body surface area (1.64 ± 0.18 vs. 1.65 ± 0.15 m2) between the two groups. The AVMPG on early postoperative echocardiography was 15.2 ± 4.6 mm Hg and 16.5 ± 6.2 mm Hg in the study and control groups, respectively (p = 0.177). Although AVMPG of the 19 mm prostheses was lower in the study group than in the control group (17.0 ± 6.3 mm Hg vs. 22.8 ± 6.6 mm Hg, p = 0.039), there were no significant differences in the effective orifice area in all patients (1.57 ± 0.41 cm2 vs. 1.53 ± 0.34 cm2, p = 0.568), and each valve size. The effective orifice area index was also similar between the two groups in overall (p = 0.352), and in each valve size. There were no significant differences in clinical outcomes including operative mortality and postoperative complications between the two groups.Conclusion Early postoperative hemodynamic and clinical results after AVR using a recently introduced bovine pericardial valve were comparable with those using the control valve (NCT03796442)
Keywords: aortic valve replacement; bioprosthesis; outcome; hemodynamics